Sosialisasi Pemasaran Dan Penggunaan Air Isi Ulang Kepada Pengusaha dan Masyarakat - Harahap, Cece (Sekolah Tinggi Ilmu Manajemen Sukma Medan, 2024)
The community's need for practical and economical drinking water has increased the dependence on Refill Drinking Water Depots (DAMIU), especially in urban areas such as Jalan Perjuangan Medan. However, this increase in consumption is not always accompanied by adequate microbiological quality assurance in accordance with health standards. This community service activity aims to socialize the importance of marketing drinking water that is fit for consumption and educate entrepreneurs and the public about the risks of bacterial contamination. The method used is descriptive qualitative with a field survey design and laboratory tests. The service team took water samples from all depots on Jalan Perjuangan to be tested at the Medan Health Laboratory Center, focusing on Escherichia coli bacterial parameters based on Minister of Health Regulation No. 492 of 2010. In addition, socialization was carried out through the distribution of health brochures and direct interviews with traders and consumers. The laboratory test results showed significant findings, where 66.7% of the samples (2 out of 3 main samples) tested positive for E. coli bacteria, thus declared not meeting the health requirements for direct consumption. The main factors of contamination are suspected to come from low employee hygiene, poorly maintained equipment sanitation, and the expiration of ultraviolet lamp life. Through this activity, the community was educated to always boil refilled water before consumption as a preventive measure. The conclusion of this service emphasizes that entrepreneurs must prioritize product safety aspects in their marketing strategy, while routine supervision from health authorities is urgently needed to guarantee the quality of drinking water at the community level.